1991
DOI: 10.1159/000243402
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of Pulmonary Sequelae after Hyaline Membrane Disease: Heterogeneity of Bronchopulmonary Dysplasia?

Abstract: In an autopsy study of 37 infants who suffered from hyaline membrane disease (HMD), two distinct patterns of pulmonary lesions could be defined. One pattern, characterized by marked interstitial fibrosis in the absence of airway abnormalities, was labelled Ê»interstitial-type’ histology. A second type, labelled Ê»bronchiolar-type’ histology, showed marked airway lesions and alveolar emphysema. Nine patients of each type were analysed. Nineteen other patients had a Ê»mixed-type’ histology and were not further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 12 publications
6
20
0
Order By: Relevance
“…This study shows for the first time that prolonged MV of the developing lung with air, without associated hyperoxia, inhibits alveolar septation and angiogenesis and is associated with increased apoptosis, activation of TGF␤, and reduced expression of VEGF-R2, a critical determinant of normal lung development. These structural and molecular changes that occurred in newborn mice after 24 h of positive-pressure MV are similar to changes that have been described in newborn infants with CLD (8,15,28,29,43,67) and in authentic animal models of this disease (2,12,18,42).…”
Section: Important Features Of This Experimental Modelsupporting
confidence: 77%
“…This study shows for the first time that prolonged MV of the developing lung with air, without associated hyperoxia, inhibits alveolar septation and angiogenesis and is associated with increased apoptosis, activation of TGF␤, and reduced expression of VEGF-R2, a critical determinant of normal lung development. These structural and molecular changes that occurred in newborn mice after 24 h of positive-pressure MV are similar to changes that have been described in newborn infants with CLD (8,15,28,29,43,67) and in authentic animal models of this disease (2,12,18,42).…”
Section: Important Features Of This Experimental Modelsupporting
confidence: 77%
“…An increase in alveolar size with fewer alveoli was found in postmortem specimens of surfactant-treated subjects by Husain et al (25) in which the MLI was significantly increased in BPD subjects compared with non-BPD. Hislop et al (23) and others (6,44) have shown that the lungs of preterm infants who received mechanical ventilation and oxy- . Quasistatic compliance (Qst) from anesthetized 13-day-old WT and MMP-9 (Ϫ/Ϫ) pups after 8 days of hyperoxia or room air exposure measured by forced oscillation technique.…”
Section: Discussionmentioning
confidence: 99%
“…Third, one of the histological hallmarks of BPD, i.e. severe airway injury, is now less frequently observed [23,24], and interstitial fibroproliferation and decreased alveolarization now predominate [25][26][27]. These features appear to be associated clinically with milder degrees of chronic respiratory distress.…”
Section: Discussionmentioning
confidence: 99%